DETERMINANTS OF GREEN PURCHASE INTENTION THROUGH THE GREEN TRUST ON FMCG PRODUCTS - Monica, Monica; Anisah, Anisah (Universitas Gunadarma, 2025)
Concern for the environment has become the main concern of organisations that encourage companies to start producing green products that are environmentally friendly because of the environmental pollution and global warming that occur. This research aims to analyse the influence of green brand positioning, green perceived value, and green marketing, through green trust, on green purchase intention for FMCG products. Identifying variables that have the most dominant influence on green trust and green purchase intention. Primary data was used in this research. The sample size is 300 respondents with a minimum purchase intensity of three times in the last six months, who are at least 17 years old and domiciled in Jabodetabek. The data analysis methods used are: validity test, reliability test, R-square test, path coefficient test, indirect effect test (path analysis), predictive relevance test, and goodness of fit model test. The research results show that the variables green brand positioning, green perceived value, and green marketing influence green trust. Green brand positioning, green perceived value, green marketing, and green trust influence green purchase intention. Green trust can mediate the relationship between green brand positioning, green perceived value, and green marketing and green purchase intention among green consumers of FMCG products. Green marketing is the dominant variable that influences the occurrence of green trust, with green trust being the dominant variable influencing green purchase intention